2019
DOI: 10.3390/ijms20194925
|View full text |Cite
|
Sign up to set email alerts
|

From Osteoclast Differentiation to Osteonecrosis of the Jaw: Molecular and Clinical Insights

Abstract: Bone physiology relies on the delicate balance between resorption and formation of its tissue. Bone resorption depends on a process called osteoclastogenesis in which bone-resorbing cells, i.e., osteoclasts, are produced by the differentiation of more undifferentiated progenitors and precursors. This process is governed by two main factors, monocyte-colony stimulating factor (M-CSF) and receptor activator of NFκB ligand (RANKL). While the former exerts a proliferating effect on progenitors/precursors, the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 109 publications
(134 reference statements)
0
46
0
15
Order By: Relevance
“…After binding of RANKL to RANK, TRAF6 is activated and forms a complex with TAK1 47 . Activated TAK1 subsequently phosphorylates the IKK/IκBα and MAPK pathways, leading to activation of the NF‐κB pathway and activated protein 1 (AP‐1) 17,18,48 . Our results showed that Corilagin suppressed the phosphorylation of NF‐κB but did not affect that of p38, ERK or JNK.…”
Section: Discussionmentioning
confidence: 64%
“…After binding of RANKL to RANK, TRAF6 is activated and forms a complex with TAK1 47 . Activated TAK1 subsequently phosphorylates the IKK/IκBα and MAPK pathways, leading to activation of the NF‐κB pathway and activated protein 1 (AP‐1) 17,18,48 . Our results showed that Corilagin suppressed the phosphorylation of NF‐κB but did not affect that of p38, ERK or JNK.…”
Section: Discussionmentioning
confidence: 64%
“…As bone deposition is required on the tension side during orthodontic tooth movement, an increased expression of BMP-2 at this site may be attributed to its role in active bone formation. RANKL is a marker for osteoclasts [29]. The expression of RANKL was mainly observed on the compression side, as opposed to the tension side ( Figure 6), indicating its role in active bone resorption.…”
Section: Discussionmentioning
confidence: 96%
“…Thereafter, the expression levels of these proteins decreased to the level of the non-treated control at 16 and 24 h (Figure 4). At 16 h, 4HR induced overexpression of RANKL (osteoclast differentiation factor) [29], RUNX2 (a key transcription factor associated with osteoblast differentiation) [30], osterix (a transcription factor for osteoblast differentiation) [31], aggrecan (a cartilage-specific proteoglycan core protein) [32], and calmodulin-dependent kinase II (a key regulator of osteoblast differentiation) [33], which co-operatively stimulated osteoblast differentiation. At 24 h, 4HR induced overexpression of BMP-3 (a negative regulator for bone density) [34], OPG (a regulator for bone density) [35], osteocalcin (a calcium-binding protein) [36], and osteopontin (bone sialoprotein I) [37], which simultaneously regulated osteoid matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF signalling might have been involved in our patient's osteitis. Other drug-induced osteonecrosis mechanisms are known such as Cyclooxygenoase 2 inhibition by non-steroid anti-inflammatory drugs and nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) inhibition by bisphosphonates [18]. Crizotinib as no direct interaction with these pathways.…”
Section: Discussionmentioning
confidence: 99%